Improving Quality of Life in Underserved Communities: A Case from Humanity Initiative's Student-Led Clinics - Syed Muhammad Aqeel Abidi; Ali Hyder Nazeer; Muhammad Mushahid Hussain Rizvi; Syeda Tayyaba Fatima Abidi (Journal of Medical Education and Curricular Development)
Using the case study of a 12-year-old girl diagnosed with complex congenital heart disease at a student-led clinic (SLC) organized by Humanity Initiative (HI) in Karachi, the paper highlights the effectiveness of SLCs in providing accessible and comprehensive healthcare services. The article contributes to existing literature by demonstrating the practical benefits of SLCs in a real-world setting, particularly in resource-limited environments. It underscores the potential of SLCs not only to improve community health but also to enhance medical education by providing students with hands-on experience and fostering a sense of social responsibility. Collaborative efforts between medical students, professionals, and the community are essential to ensure the continuity and effectiveness of healthcare interventions. For the success of such initiatives, there is a need for sustainable funding, effective follow-up protocols, and reliable communication channels with patients, offering solutions like peer mentoring and technology integration to overcome these barriers.